2015
DOI: 10.1016/j.trsl.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes of soluble CD40 ligand in the progression of acute myocardial infarction associate to endothelial nitric oxide synthase polymorphisms and vascular endothelial growth factor but not to platelet CD62P expression

Abstract: Abbreviations: AMI ¼ acute myocardial infarction; APC ¼ allophycocyanin; Asp ¼ aspartate; cTNT ¼ cardiac troponin; CAD ¼ coronary artery disease; CRP ¼ C-reactive protein; CK ¼ creatine kinase; eNOS ¼ endothelial nitric oxide synthase; ELISA ¼ enzyme-linked immunosorbent assay; FITC ¼ fluorescein isothiocyanate; FAU ¼ fluorescence arbitrary units; Glu ¼ glutamic acid; LME ¼ linear mixed effects model; MPs ¼ microparticles; NO ¼ nitric oxide; NT-proBNP ¼ N-terminal pro-brain natriuretic peptide; PCI ¼ percutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…Previous studies using this cohort indicated that influence of medication in the values of inflammatory markers lasted for several days after PCI. 5,13 Therefore, patients' assessment 1 month after PCI represents the period of time for medication and clinical stabilization.…”
Section: Translational Significancementioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies using this cohort indicated that influence of medication in the values of inflammatory markers lasted for several days after PCI. 5,13 Therefore, patients' assessment 1 month after PCI represents the period of time for medication and clinical stabilization.…”
Section: Translational Significancementioning
confidence: 99%
“…Having into consideration our previous exploratory analysis, 5 serum was chosen to determine sCD40L by enzyme-linked immunosorbent assay. In addition, to safeguard sCD40L stability, temperature was kept at 4 C in all steps after blood collection, that is, transport and processing.…”
Section: Translational Significancementioning
confidence: 99%
See 3 more Smart Citations